2023
DOI: 10.1590/s1677-5538.ibju.2023.0031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different combinations of radical nephroureterectomy and bladder cuff excision procedures for upper tract urothelial carcinoma on bladder recurrence

Abstract: Purpose: To compare the effects of different combinations of radical nephroureterectomy (RNU) and bladder cuff excision (BCE) surgical procedures on intravesical recurrence (IVR) in patients with upper tract urothelial carcinoma (UTUC). Materials and Methods: This retrospective observational study included 452 patients who underwent RNU with BCE for UTUC between January 2010 and December 2020. The patients were classified into three groups based on different combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Dr. Huang and Collegues form Taiwan performed on page 469 ( 5 ) a nice study about the effects of Different Combinations of Radical Nephroureterectomy and Bladder Cuff Excision Procedures for Upper Tract Urothelial Carcinoma on Bladder Recurrence and concluded that patients with upper tract urothelial carcinoma, minimally invasive (MIS) radical nephroureterectomy (RNU) with open bladder cuff excision (BCE) is associated with a higher risk of intravesical recurrence than open RNU with open BCE and MIS RNU with intracorporeal BCE.…”
mentioning
confidence: 99%
“…Dr. Huang and Collegues form Taiwan performed on page 469 ( 5 ) a nice study about the effects of Different Combinations of Radical Nephroureterectomy and Bladder Cuff Excision Procedures for Upper Tract Urothelial Carcinoma on Bladder Recurrence and concluded that patients with upper tract urothelial carcinoma, minimally invasive (MIS) radical nephroureterectomy (RNU) with open bladder cuff excision (BCE) is associated with a higher risk of intravesical recurrence than open RNU with open BCE and MIS RNU with intracorporeal BCE.…”
mentioning
confidence: 99%